The Artificial Silicon Retina in Retinitis Pigmentosa Patients (An American Ophthalmological Association Thesis) - Chow, Alan Y. (The American Ophthalmological Society, 2010)
PURPOSE: In a published pilot study, a light-activated microphotodiode-array chip, the artificial silicon retina (ASR), was implanted subretinally in 6 retinitis pigmentosa (RP) patients for up to 18 months. The ASR electrically induced retinal neurotrophic rescue of visual acuity, contrast, and color perception and raised several questions: (1) Would neurotrophic effects develop and persist in additionally implanted RP patients? (2) Could vision in these patients be reliably assessed? (3) Would the ASR be tolerated and function for extended periods? METHODS: Four additional RP patients were implanted and observed along with the 6 pilot patients. Of the 10 patients, 6 had vision levels that allowed for more standardized testing and were followed up for 7+ years utilizing ETDRS charts and a 4-alternative forced choice (AFC) Chow grating acuity test (CGAT). A 10-AFC Chow color test (CCT) extended the range of color vision testing. Histologic examination of the eyes of one patient, who died of an unrelated event, was performed. RESULTS: The ASR was well tolerated, and improvement and/or slowing of vision loss occurred in all 6 patients. CGAT extended low vision acuity testing by logMAR 0.6. CCT expanded the range of color vision testing and correlated well with PV-16 (r = 0.77). An ASR recovered from a patient 5 years after implantation showed minor disruption and excellent electrical function. CONCLUSION: ASR-implanted RP patients experienced prolonged neurotrophic rescue of vision. CGAT and CCT extended the range of acuity and color vision testing in low vision patients. ASR implantation may improve and prolong vision in RP patients.